Crystal Phase Transitions in the Shell of PbS/CdS Core/Shell Nanocrystals Influences Photoluminescence Intensity - Lechner, Rainer T.; Fritz-Popovski, Gerhard; Yarema, Maksym; Heiß, Wolfgang; Hoell, Armin; Schuelli, Tobias U.; Primetzhofer, Daniel; Eibelhuber, Martin; Paris, Oskar (Chemistry of Materials, 2014)
We reveal the existence of two different crystalline phases, i.e., the metastable rock salt and the equilibrium zinc blende phase within the CdS-shell of PbS/CdS core/shell nanocrystals formed by cationic exchange. The chemical composition profile of the core/shell nanocrystals with different dimensions is determined by means of anomalous small-angle X-ray scattering with subnanometer resolution and is compared to X-ray diffraction analysis. We demonstrate that the photoluminescence emission of PbS nanocrystals can be drastically enhanced by the formation of a CdS shell. Especially, the ratio of the two crystalline phases in the shell significantly influences the photoluminescence enhancement. The highest emission was achieved for chemically pure CdS shells below 1 nm thickness with a dominant metastable rock salt phase fraction matching the crystal structure of the PbS core. The metastable phase fraction decreases with increasing shell thickness and increasing exchange times. The photoluminescence intensity depicts a constant decrease with decreasing metastable rock salt phase fraction but shows an abrupt drop for shells above 1.3 nm thickness. We relate this effect to two different transition mechanisms for changing from the metastable rock salt phase to the equilibrium zinc blende phase depending on the shell thickness. © 2014 American Chemical Societ
Keywords: Core/shell nanocrystals; Crystal phase transition; Photoluminescence intensities